A discrete organoplatinum(II) metallacage as a multimodality theranostic platform for cancer photochemotherapy. Issue 1 (December 2018) - Yu, Guocan; Yu, Shan; Saha, Manik; Zhou, Jiong; Cook, Timothy; Yung, Bryant; Chen, Jin; Mao, Zhengwei; Zhang, Fuwu; Zhou, Zijian; Liu, Yijing; Shao, Li; et al.
Abstract Photodynamic therapy is an effective alternative to traditional treatments due to its minimally invasive nature, negligible systemic toxicity, fewer side effects, and avoidance of drug resistance. However, it is still challenging to design photosensitizers with high singlet oxygen (1 O2 ) quantum yields (QY) due to severe aggregation of the hydrophobic photosensitizers. Herein, we developed a discrete organoplatinum(II) metallacage using therapeuticcis -(PEt3 )2 Pt(OTf)2 as the building block to improve the1 O2 QY, thus achieving synergistic anticancer efficacy. The metallacage-loaded nanoparticles (MNPs) with tri-modality imaging capability allow precise diagnosis of tumor and real-time monitoring the delivery, biodistribution, and excretion of the MNPs. MNPs exhibited excellent anti-metastatic effect and superior anti-tumor performance against U87MG, drug resistant A2780CIS, and orthotopic tumor models, ablating the tumors without recurrence after a single treatment. Gene chip analyses confirmed the contribution of different therapeutic modalities to the tumor abrogation. This supramolecular platform holds potential in precise cancer theranostics. It is challenging to design photosensitizers (PS) with high quantum yields generating singlet oxygen due to severe aggregation between the hydrophobic PSs. Here they develop organoplatinum(II) metallatocage-based PS to overcome these challenges and show excellent antitumor effect.